Magma storage, transport and degassing during the 2008-10 summit eruption at Kilauea Volcano, Hawai'i - Edmonds, M; Sides, I; Swanson, D; Werner, C; Martin, R; Mather, T; Herd, R; Jones, R; Mead, M; Sawyer, G; Roberts, T; Sutton, A; et al. (2013)
The 2008-current summit eruption at Kīlauea Volcano, Hawai'i offers a unique opportunity to test models of degassing and magma plumbing and to improve our understanding of the volatile budget. The aim of this work was to test the hypothesis that gases emitted from a summit lava lake will be rich in carbon dioxide (CO) and similar to those measured during the persistent lava lake activity in the early 20th century at Kīlauea Volcano (Gerlach and Graeber, 1985). We measured the sulfur dioxide (SO) and CO concentrations in the gas plume from Halema'uma'u using electrochemical and non-dispersive infrared sensors during April 2009. We also analysed olivine-hosted melt inclusions from tephra erupted in 2008 and 2010 for major, trace and volatile elements. The gas and melt data are both consistent with the equilibration of a relatively evolved magma batch at depths of 1.2-2.0 km beneath Halema'uma'u prior to the current degassing activity. The differences in the volatile concentrations between the melt inclusions and matrix glasses are consistent with the observed gas composition. The degassing of sulfur and halogen gases from the melt requires low pressures and hence we invoke convection to bring the magma close to the surface to degas, before sinking back into the conduit. The fluxes of gases (900 and 80 t/d SO and CO respectively) are used to estimate magma fluxes (1.2-3.4 m/s) to the surface for April 2009. The observation of minimal loss of hydrogen from the melt inclusions implies a rapid rise rate (less than a few hours), which constrains the conduit radius to 1-2 m. The inferred conduit radius is much narrower than the lava lake at the surface, implying a flared geometry. The melt inclusion data suggest that there is a progressive decrease in melt volatile concentrations with time during 2008-2010, consistent with convection, degassing and mixing in a closed, or semi-closed magma system. The degassing regime of the current summit lava lake activity is not similar to that observed in the early 20th century; instead the gases are extensively depleted in CO. © 2013 The Authors.